The Burden of Undernutrition and Its Associated Factors Among Children Below 5 Years of Age in Bambao Region, Comoros - Ahamada, Hadji; Sunguya, Bruno F. (Frontiers in Nutrition, 2022)
Background: Undernutrition remains a major public health problem in low-income countries, Comoros is no exception. This study aimed to examine the prevalence and identify the risk factors of undernutrition among children under-five years in Bambao region, Comoros. Methods: This cross-sectional study conducted in Bambao region collected data from 837 under-five years and their caregivers. Analyses were conducted using both descriptive and logistic regression to examine the magnitude and factors associated with stunting, wasting and underweight. Results: Prevalence of stunting, wasting and underweight were estimated to be 21.6%, 13.7%, and 13.6% respectively. Factors associated with stunting were caregiver’s secondary education level compared to no education (AOR=1.89, 95% CI: 1.04-3.43, P<0.04), age of child between 13-24 months compared to 0-12 months (AOR=2.69, 95% CI: 1.44-5.01, P<0.001), and food insecurity (AOR=2.55, 95% CI: 1.20-5.41, P<0.02). Factors associated with wasting included age of child between 25-59 months with a decreased odds compared to those with 0-12 months (AOR=0.22, 95% CI: 0.10-0.51, P<0.001), food insecurity (AOR=2.70, 95% CI: 1.12-6.49, P<0.03), and low birthweight (AOR=3.21, 95% CI: 1.73-5.94, P<0.001). Children aged between 25-59 months had a lower risk of underweight compared to those aged 0-12 months (AOR=0.14, 95% CI: 0.06-0.36, P<0.001). Food insecurity (AOR=2.65, 95% CI: 1.08-6.54, P<0.03), low birthweight (AOR=3.15, 95% CI: 1.67-5.93, P<0.001), and non-exclusively breastfeeding (AOR=2.37, 95% CI: 1.15-4.90, P<0.02) were independent risk factors for underweight. Conclusion: Undernutrition among under-fives years is high in Comoros. Addressing this burden calls for streamlined efforts to address poor feeding practices, food insecurity, low birth weight, and socio-demographic disadvantages in this and other areas with similar context.